Sugarcane cultivation through Sustainable Sugarcane Initiative - Chandrasekaran, R.; Suveetha, M.; Pandian, B. J.; Sampathkumar, T.; Muralidharan, S. (Indian Farming, 2015)
SSI involves use of less seeds, less water and optimum land utilization to achieve more yields. It is governed by some principles like using single budded chips, raising nursery, wider spacing, sufficient irrigation and intercropping. Benefits can be realized practising these measures. Farmers can realize the increased yield and reduce the use of inputs like fertilizers along with water saving. SSI is a yield increasing and resource saving technology which farmers can easily adopt and reap more income.